Human pigmentation: A side effect adapted from a primitive organism's survival. Part 2: The melanocyte as mentor of the keratinocye - Sanju Arianayagam; Terence J Ryan (Wolters Kluwer Medknow Publications, 2014)
Pigmentation featured millions of years ago and perhaps began with an amoeba frightening off a predator with some agent such as dopamine to prevent its attachment for phagocytosis by an enemy. This paper suggests that the environmental forces of grip and stick, rather than pure chemical influences, deserve greater emphasis, and that the influence of the mechanical forces involved in grip and stick or release from attachment, all point to control of proteases as a function underlying pigmentation. How and why pigmentation varies with temperature and sunlight is discussed. The toxicity of melanin, pH, transepidermal water loss, and the influence of endocrine factors are also addressed.